Interpretation in Classroom Listening - Waks, Leonard (Philosophical Inquiry in Education, 2024)
Sophie Haroutunian-Gordon and the author have debated about the meaning of listening in education. For Haroutunian-Gordon, listening implies mental acts of questioning. By contrast, the author has offered a dual process account of listening, distinguishing between listening that involves explicit, consciously directed mental effort and listening that is direct and immediate and requires no effort.  The topic of “interpretation in listening” offers an opportunity for further consideration of these two types of listening. We can ask whether listeners are  always interpreting speakers’ utterances, or whether there are some acts of listening that are immediate and direct, and thus do not involve interpretation. This paper argues, based on a close analysis of the concept of listening, that many typical acts of listening in classrooms are of the second, immediate, type.